1977
DOI: 10.1111/j.1365-2621.1977.tb08453.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baking Methods on the Fatty Acid Composition of Potatoes

Abstract: Fatty acid analysis Only minor differences in overall relative fatty acid composition were noted among four varieties of potatoes baked by microwave and conventional methods. However, the relative percent total unsaturated fatty acids were consistently lower in the microwave products as compared to conventionally baked potatoes regardless of variety. In addition, the relative percent rrans fatty acids was 2.5-4 times higher in the microwave process compared to the same varieties baked conventiohally.Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Contradictory results have been reported on the possible isomerization (formation of trans) in the double bonds of fatty acids as a consequence of exposure to microwave energy (Maga et al, 1977;Mai et al, 1980), and in no study have data appeared relating to the positional isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory results have been reported on the possible isomerization (formation of trans) in the double bonds of fatty acids as a consequence of exposure to microwave energy (Maga et al, 1977;Mai et al, 1980), and in no study have data appeared relating to the positional isomers.…”
Section: Introductionmentioning
confidence: 99%
“…During stir-frying the oil was heated at an elevated temperature for a short time. In baking and stir-frying the fat was protected by water present in the prepared food, which lowers the temperature to a maximum of 100 o C. Maga et al (16) observed similar and insignificant changes in trans fat formation during the baking of potatoes. The activation energy for PUFA isomerization decreases when the number of cis double bonds increases (2,20); hence the linolenic acid trans isomers dominate in trans fat.…”
Section: Discussionmentioning
confidence: 90%
“…Thermo-oxidative degradation of lipids during food preparation at elevated temperatures has been studied extensively (12)(13)(14)(15); however, data are limited on the effect of these cooking methods on the formation of trans fats (15,16). Currently, baked goods are the main dietary source of trans fats, and reformulation of baking fats with liquid oils containing higher amounts of PUFA has the potential to increase trans fat formation during baking (15,17).…”
Section: Introductionmentioning
confidence: 98%
“…Although the unknown HPLC peak eluting almost at the end of the solvent gradient in an ordinary HPLC separation can be confused with PPD, which is the most non-polar ginsenoside, we successfully showed that it is not a ginsenoside but rather linoleic acid by using analytical techniques such as LC-MS/MS and NMR. In addition, free fatty acids are known to usually increase in processed foods such as baked potato [30] and cooked pork [31]; thus, the hydrothermal degradation of lipids seems responsible for the increased free fatty acid content of black ginseng products.…”
Section: Discussionmentioning
confidence: 99%